PEMBERDAYAAN ORANG DENGAN GANGGUAN JIWA (ODGJ) DALAM MENGENDALIKAN RESIKO PERILAKU KEKERASAN DI WILAYAH KERJA PUSKESMAS BABAKAN SARI KOTA BANDUNG - Fatah, Vera Fauziah; Z, Desmaniarti; Sasmita, Anah (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
People with mental disorders (ODGJ) in Indonesia have increased. In West Java, 11.360 people suffered from severe mental disorders in 2017 and increased to 16.714 in 2018. Some ODGJ are treated in psychiatric hospitals because of violent behavior and when they are declared cured after being at home they are very at risk of violent behavior, so they need special handling as a form of prevention of mental disorders. To prevent this, ODGJ should be empowered to control their behavior, especially the risk of violent behavior, so that something unwanted does not happen. Handling ODGJ with the risk of violent behavior can be done with a prevention program, namely religious therapy: listening to audio murottal Al-Qur'an and deep breath relaxation. The deep breath relaxation and murottal Al-Qur'an techniques listened to through audio not only cause a calming effect on the physical body but also calm the mind so that it can reduce the risk of violent behavior. This community service aims to empower cadres and ODGJ in reducing signs of risk of violent behavior in Sukapura Village, Babakan Sari Health Center Working Area, Bandung City. This activity began with training 10 health cadres to help empower 16 ODGJ in helping to reduce signs of risk of violent behavior by listening to deep breath relaxation audio and murottal Al-Qur’an: Surat Al-Fatihah twice a day for 2 weeks. The results and outcomes of this activity are an increase in cadre knowledge related to the risk of violent behavior and how to control it and a decrease in feelings of risk of violent behavior in ODGJ.